ANALISIS URAIAN TUGAS TENAGA ADMINISTRASI SEKOLAH BIDANG PERSURATAN DAN PENGARSIPAN DI SLTA SE- KABUPATEN TANAH DATAR - Yulia Fitri; Rusdinal Rusdinal; Novriyanti Achyar; Merika Setiawati (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the job description of school administrative staff in the correspondence and archiving division at senior high schools in Tanah Datar Regency based on the aspects of task clarity, work responsibility, authority, and work procedures. Method: This study employed a descriptive method with a quantitative approach. The population consisted of 63 school administrative staff, with a sample of 54 respondents determined using the Slovin formula through a simple random sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability, and were analyzed using descriptive statistics through mean scores and the Respondent Achievement Level (TCR). Results: The results showed that task clarity obtained an average score of 4.30 (TCR 86.04%), work responsibility 4.29 (85.80%), authority 4.28 (85.68%), and work procedures 4.18 (83.62%). Overall, the job description of school administrative staff in the correspondence and archiving division was categorized as good, although the work procedure aspect still requires improvement. Novelty: The novelty of this study lies in presenting an empirical overview of the job description of school administrative staff in the correspondence and archiving division based on four main aspects at senior high schools in Tanah Datar Regency, which can serve as a basis for evaluating and improving school administrative management.